The role of national committees in eliminating onchocerciasis. (19th February 2018) - Griswold, Emily; Unnasch, Thomas; Eberhard, Mark; Nwoke, Bertram E B; Morales, Zoraida; Muheki Tukahebwa, Edridah; Kebede, Biruck; Anagbogu, Ifeoma; Katabarwa, Moses; Habomugisha, Peace; Tadesse, Zerihun; Miri, Emmanuel S; et al.
Abstract: National onchocerciasis elimination committees (NOECs) serve to help ministries of health complete the pathway to successful verification of elimination of onchocerciasis (river blindness), as outlined in the 2016 World Health Organization guidelines. These guidelines, however, only take effect when the country believes it has reached a point that elimination can be demonstrated, and do not address the preceding milestones. Therefore, NOECs can be of great help with guiding and tailoring earlier planning, programming and assessments to empower national programs to aggressively move toward their countries' elimination goals. In this article, we provide suggestions for organizing NOECs and examples of four such committees that have successfully operated in Africa and the Americas.